ECOLOGICAL HOMEORHESIS IN THE MECHANISM OF FORMATION OF ANTHROPONOSES VIRULENCE - A. V. Dubov (Детские инфекции (Москва))
Peculiarities of formation of ecological homeorhesis i.e. coming into compliance with environmental factors of homeostasis systems at population, species and interspecific levels are determined at anthroponoses. The features of the evolution, epidemiology and clinical course of anthroponoses (for example, measles) when influencing on man-virus system in a series of generations of extremely high or low temperatures of air and elimination of the virus on vast territories are pointed out.